Interfacial engineering of a PAN-PBAs-PA composite membrane with secondary Ni2+ curing for highly selective removal of cesium - Lixing Lin; Xiaoxia Sun; Qingshan Liu; Guoquan Zhou; Congjie Gao; Jia Xu (Desalination, 2026)

Dissecting photo-assisted and light-only charging mechanisms in lithium-ion batteries enabled by hierarchical Ni/TiO2@CdS/Ni3S2 photoelectrodes - Meng Wei; Guangyu Lin; Qianwen Dong; Qiongzhi Gao; Xin Cai; Shengsen Zhang; Lixing Ding; Feng Peng; Xiaosong Zhou; Siyuan Yang (Chemical Engineering Journal, 2026)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Nanozymes design via cost-sensitive machine learning for antibacterial applications - Tianliang Li; Xiao Zhang; Xinting Liu; Lixing Lin; Yuze Ren; Zeyu Li; Yingying Chen; Zhenzhen Li; Lingyan Feng (Chemical Engineering Journal, 2025)

Dynamic adaptations: Unraveling the skin microbiome of bullfrogs (Rana catesbeiana) under bacterial disease stress - Shan Hu; Gongshi Lin; Theerakamol Pengsakul; Lixing Huang (Aquaculture, 2025)

Dietary spermine supplementation enhances growth, protein synthesis, and antioxidant capacity in hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) - Lina Geng; Chirun Lin; Guojian Pan; Yusen Yang; Lixing Wang; Shengming Huang; Zhiyu Zhou; Haoran Yin; Xiaoyi Wu (Aquaculture, 2025)

“Three-birds, one-stone” biomimetic nanozyme system based on oxygen vacancy structure-regulated cascade reaction for inflammatory bowel disease - Tianliang Li; Zhaoming Wang; Zhijie Wang; Yihuan Pu; Lixing Lin; Zeyu Li; Lifei Chen; Xinting Liu; Bin Cao; Yingying Chen; Zhenzhen Li; Zixuan He; et al. (Chemical Engineering Journal, 2025)

A flame-retardant and weakly solvated gel electrolyte for high-performance and high-safety Ah class sodium-ion batteries - Lixing Xue; Hongyan Pan; Yuejun Wang; Zhengyi Wang; Xuhui Wang; Qian Lin; Kuo Zhang; Xiangnan Bu; Maohui Bai; Bo Hong (Chemical Engineering Journal, 2025)

Antibiotic Resistance in Vibrio parahaemolyticus : Mechanisms, Dissemination, and Global Public Health Challenges—A Comprehensive Review - Yingpeng Li; Gongshi Lin; Theerakamol Pengsakul; Qingpi Yan; Lixing Huang (Reviews in Aquaculture, 2025)
Vibrio parahaemolyticus , a ubiquitous pathogen in marine and estuarine environments, is a foodborne microorganism whose infections have become a global public health challenge. In recent years, the overuse and misuse of antibiotics have led to the emergence of increasing numbers of antibiotic‐resistant strains of V. parahaemolyticus worldwide. These strains harbor resistance genes that mediate various resistance mechanisms, presenting a significant challenge to antibiotic therapy. Furthermore, horizontal gene transfer (HGT) of resistance genes and the accelerating impacts of global climate change have facilitated the formation and spread of resistance, contributing to the proliferation of resistant strains and exacerbating the public health threat. This review aims to provide a comprehensive overview of the resistance genes and mechanisms in V. parahaemolyticus , the effects of climate change on its resistance, and strategies to curb the transmission of resistant strains. Additionally, we conducted a statistical analysis of resistance data from 6727 V. parahaemolyticus isolates obtained from 27 countries across Asia, Africa, the Americas, and Europe, through the literature review, to better understand the distribution and trends of resistance in this pathogen. We hope that this study will serve as an important reference for controlling the spread of antibiotic resistance in V. parahaemolyticus and addressing this critical public health issue.

Investigating the generation mechanism of nanobubbles and the ion-transport regulation on nanofiltration membranes for efficient salt-salt separation - Shiyi Yao; Hansi Zhang; Kaiwen Wang; Lixing Lin; Xiaoxia Sun; Jia Xu (Journal of Cleaner Production, 2024)

On-device charge engineering in 2D perovskite oxides for high performance photodetectors - Yong Zhang; Lin Wang; Xiujun Wang; Xiaohang Pan; Pin Zhao; Ye Liu; Qing Guo; Lixing Kang; Xiaosheng Fang (Chemical Engineering Journal, 2024)

Concept and investigation of Selective Forward Osmosis (SFO) for Salt-Salt Separation as a Pretreatment of Seawater for Resource Utilization - Xiaoxia Sun; Hansi Zhang; Feng Sun; Lishan Xu; Lixing Lin; Jia Xu (Water Research, 2024)

Identification of antibiotic-resistance markers of Edwardsiella tarda using aptamers - Yunting Fan; Jiang Zheng; Mao Lin; Qibiao Weng; Lixing Huang; Qingpi Yan (Food Bioscience, 2024)

Whole-rock geochemical and zircon U-Pb-Hf isotopic compositions of the Yunlougang and Wucun granitic plutons in the Hetai area of South China: Implications for petrogenesis and geodynamic setting - Lixing Wang; Deru Xu; Hai Lin; Xinyu Wang; Genwen Chen; Qianqian Jiao (Geochemistry, 2024)

Can hot water injection with chemical additives be an alternative to steam injection: Static and dynamic experimental evidence - Xuan Du; Tong Liu; Changfeng Xi; Bojun Wang; Zongyao Qi; You Zhou; Jiacheng Xu; Lixing Lin; Georgeta Istratescu; Tayfun Babadagli; Huazhou Andy Li (Fuel, 2023)

Soil plant-available phosphorus levels and maize genotypes determine the phosphorus acquisition efficiency and contribution of mycorrhizal pathway - Qun Chu; Lin Zhang; Jianwei Zhou; Lixing Yuan; Fanjun Chen; Fusuo Zhang; Gu Feng; Zed Rengel (Plant and Soil, 2020)

A 3‐hydroxy‐3‐methylglutaryl‐CoA synthase‐based probe for the discovery of the acyltransferase‐less type I polyketide synthases - Haoyu Liang; Lin Jiang; Qiyun Jiang; Jie Shi; Jingxi Xiang; Xiaohui Yan; Xiangcheng Zhu; Lixing Zhao; Ben Shen; Yanwen Duan; Yong Huang (Environmental Microbiology, 2019)
Summary Acyltransferase (AT)‐less type I polyketide synthases (PKSs) produce complex natural products due to the presence of many unique tailoring enzymes. The 3‐hydroxy‐3‐methylglutaryl coenzyme A synthases (HCSs) are responsible for β ‐alkylation of the growing polyketide intermediates in AT‐less type I PKSs. In this study, we discovered a large group of HCSs, closely associated with the characterized and orphan AT‐less type I PKSs through in silico genome mining, sequence and genome neighbourhood network analyses. Using HCS‐based probes, the survey of 1207 in‐house strains and 18 soil samples from different geographic locations revealed the vast diversity of HCS‐containing AT‐less type I PKSs. The presence of HCSs in many AT‐less type I PKSs suggests their co‐evolutionary relationship. This study provides a new probe to study the abundance and diversity of AT‐less type I PKSs in the environment and microbial strain collections. Our study should inspire future efforts to discover new polyketide natural products from AT‐less type I PKSs.

Triple medium physical model of post fracturing high-rank coal reservoir in southern Qinshui Basin - Shiqi Liu; Shuxun Sang; Qipeng Zhu; Jiefang Zhang; Hefeng Gao; Huihu Liu; Lixing Lin (Journal of Earth Science, 2015)

Investigation of possible molecular mechanisms underlying the regulation of adhesion in Vibrio alginolyticus with comparative transcriptome analysis - Wendi Kong; Lixing Huang; Yongquan Su; Yingxue Qin; Ying Ma; Xiaojin Xu; Mao Lin; Jiang Zheng; Qingpi Yan (Antonie van Leeuwenhoek, 2015)